PENGARUH KETERLIBATAN ORANG TUA DALAM BELAJAR TERHADAP PRESTASI BELAJAR SISWA SEKOLAH DASAR NEGERI PINTUKISI - Safitri, Ayu; Azwar Uswatun, Din; Lyesmaya, Dyah (STKIP Subang, 2020)
The purpose of this study is to describe the influence of parental involvement on learning achievement in the Pintukisi Public Elementary School in Sukabumi City. This research was conducted at the Pintukisi Public Elementary School in Sukabumi City. The method used in this research is quantitative method. The type of research used is ex post facto. Data collection techniques that researchers use in this study are observation, interviews, questionnaires, and documentation. The sampling technique used is the probability sampling type of random sampling and in this case there are 30 students and 30 parents. In this study, data analysis used is correlation statistical analysis, analysis prerequisite test, and final analysis or hypothesis testing. The results showed that there was an influence of parental involvement on learning achievement in Pintukisi Public Elementary School, Sukabumi City. The magnitude of the effect of parental involvement in learning on student achievement is high with an R coefficient of 0.731. The contribution of variable X to Y was 0.508 or 50.8% then the remaining 49.2% was determined by other factors.